Uji Toksisitas Perkembangan Siprofloksasin dan Studi Histologi Terhadap Mencit Putih - Zakiah, Noni; Almahdy, Almahdy; Muchtar, M. Husni (Jurnal Sains dan Teknologi Farmasi, 2012)
A study was conducted to determine the âdevelopment toxicityâ of ciprofloxacin and litters kidney. The aim of this study was to observe teratogenic effect of ciprofloxacin, and observing its effect on behaviour development and litters kidney. Twenty four pregnant mice were divided into 4 groups : control, and treatments with oral dose of ciprofloxacin of 14,3 mg, 28,5 mg, and 57,1 mg/kg body weight/day for 10 days, coincided with sixth day until fifteenth day of pregnancy for prenatal and posnatal test. Half of the animals were killed on day 18 of gestation and the others half were allowed to deliver. Fetuses were removed by caesarean section. For postnatal test, ciprofloxacin exposed at first day of lactation until weaning. Behaviour toxicity was conducted by Behavioral Test Battery, and observing its effect on litters kidney by paraffin method. Quantitative data were analyzed with Anova and Duncanâs Multiple Range Test. Results showed that teratogenic effects of ciprofloxacin were fetuses death, resorption and hemorrhage. For behaviour toxicity, delayed ability was noticed at 28,5 mg/kg BW obviously, histologically there were disturbances of kidney, which were the thickening of bowmanâs capsule, constriction of glomerular capillaries and necrosis.